1992
DOI: 10.1002/jnr.490330215
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic relationships between proteins of myelin and paranodally shedded, partially degraded myelin fragments in the rabbit CNS

Abstract: The "close-to-node" regions of myelinated nerve fibres, i.e., the paranodal end segments, are generally thought to be sites of high metabolic activity and myelin sheath turnover. Data on turnover rates of individual myelin constituents are conflicting but there exists a common belief that myelin is metabolized as independent molecules rather than as a unit. The occurrence of paranodal Marchi-positive bodies, with morphological and biochemical properties consistent with partially degraded myelin, prompted us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…In contrast, the number of mitochondria estimated in larger Schwann cell paranodal loops ranges from a few hundreds to thousands per node (Rydmark, Berthold, & Gatzinsky, 1998). Past studies argued that CNS paranodal loops lack mitochondria (Corneliuson, Berthold, Fabricius, Gatzinsky, & Carlstedt, 1989;Hildebrand, 1971;Persson, Berthold, Rydmark, & Fabricius, 1992), but recent findings (Rinholm et al, 2016) and the present study suggest that mitochondria may be recruited by signaling at CNS paranodal junctions.…”
Section: Mitochondria Are Recruited To Local Enrichments Of Netrin-contrasting
confidence: 60%
“…In contrast, the number of mitochondria estimated in larger Schwann cell paranodal loops ranges from a few hundreds to thousands per node (Rydmark, Berthold, & Gatzinsky, 1998). Past studies argued that CNS paranodal loops lack mitochondria (Corneliuson, Berthold, Fabricius, Gatzinsky, & Carlstedt, 1989;Hildebrand, 1971;Persson, Berthold, Rydmark, & Fabricius, 1992), but recent findings (Rinholm et al, 2016) and the present study suggest that mitochondria may be recruited by signaling at CNS paranodal junctions.…”
Section: Mitochondria Are Recruited To Local Enrichments Of Netrin-contrasting
confidence: 60%
“…2003) and in brain stem myelin, as demonstrated in the present study. Using metabolic labeling studies, degraded myelin proteins originally found in the intact fraction can be demonstrated within the floating fraction (Persson 1991; Persson and Karlsson 1991; Persson et al . 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of myelin fractions from brain white matter revealed that the protein content of the floating myelin fraction, which has been shown to contain degraded myelin protein (Persson and Corneliuson 1989; Persson and Karlsson 1991; Persson et al . 1992), increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of myelin fractions from brain white matter revealed that the protein content of the floating myelin fraction, which has been shown to contain degraded myelin protein (Persson and Corneliuson 1989;Persson and Karlsson 1991;Persson et al 1992), increased with age. In addition to aging, it is noteworthy that increased amounts of floating myelin have been demonstrated in inflammatory and demyelinating diseases of brain white matter, perhaps as a result of inflammatory injury to the myelin membrane (Norton and Cammer 1984b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation